ESTIMATION OF WATER BALANCE UNDER THE CONDITIONS OF CROPS GROWING ON DRY PEAT SOILS OF POLISSІA ZONE - Tsuman, N.; Sуvko, Yu.; Prohozhuk, R.; Kruchok, I. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The paper presents the data concerning the researches which point out to the fact that the soil water flow plays an important role in the natural conditions biological complex as well as in the amelioration practice. The intensity of the soil water-intake process has been characterized by its variability and depends on the porousness, mechanical, mineral, chemical composition as well as on its cultivation, soil spaces, cracks, moles, roots and other openings. The water balance of meliorated soils includes some components such as the precipitation, surface and subsurface waters, which comes from he nearest headers, infiltrated rivers and storages lakes waters as well as from condensed waters, transpiration, soil and water surface evaporation in particular. The research of the matter needs the detail scientific substantiation under the conditions of different crops growing on dry soils of Polissya zone. The water balance of crops growing on dry peat soils during the vegetation period for the layer of 0-50 cm has been investigated. The calculations showed that the process of water supply optimization on dry peat soils had an essential effect on its yielding level, herewith the crops efficiency under the regulated and controlled soils water levels increased greatly. Natural LSW comprise to special years as well as to the periods of plant vegetation. In this case, the methods of moisture intensive management and modelling usage, can supply plant biological necessity under the efficient and qualitative yielding formation. The optimal moisture under the layer of 0-50 cm on dry peat soils during the period of yield forming for the perennial grasses and vetch-oat mixtures made up 77-89%. It has become possible to achieve the highest efficiency of crops green mass due to a given moisture parameters.